1999
DOI: 10.1161/01.str.30.11.2268
|View full text |Cite
|
Sign up to set email alerts
|

Initial Loss of Consciousness and Risk of Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Delayed cerebral ischemia (DCI) is a major cause of death and disability in patients with aneurysmal subarachnoid hemorrhage. We studied the prognostic value for DCI of 2 factors: the duration of unconsciousness after the hemorrhage and the presence of risk factors for atherosclerosis. Methods-In 125 consecutive patients admitted within 4 days after hemorrhage, we assessed the presence and duration of unconsciousness after the hemorrhage, the neurological condition on admission, the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 28 publications
2
56
1
3
Order By: Relevance
“…Thirty-three studies (63%) were rated as HQ. [9][10][11][12][13]15,16,[18][19][20]22,[28][29][30][31]35,36,38,39,[41][42][43]46,[48][49][50][51][52][53][54][55][56][57] Appendix 1 summarizes the study characteristics and the investigated variables. Altogether, 33 variables were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies (63%) were rated as HQ. [9][10][11][12][13]15,16,[18][19][20]22,[28][29][30][31]35,36,38,39,[41][42][43]46,[48][49][50][51][52][53][54][55][56][57] Appendix 1 summarizes the study characteristics and the investigated variables. Altogether, 33 variables were reported.…”
Section: Resultsmentioning
confidence: 99%
“…2 It occurs in approximately one third of patients, mostly between the fourth and the tenth days after the hemorrhage. 3,4 Independent predictors for DCI are the neurological condition on admission and the amount of extravasated blood on the initial CT. [5][6][7] In a recent study, we also found that cerebral perfusion on the admission CT is a strong predictor for the development of DCI. 8 Because it is plausible that acute hydrocephalus has a negative influence on the cerebral perfusion, hydrocephalus on the admission scan may be a risk factor for DCI as well.…”
mentioning
confidence: 73%
“…The period of loss of consciousness indicates global ischemia. Hop et al (13) claim that LOC is a strong predictor of the occurrence of DCI.…”
Section: Loss Of Consciousness (Loc)mentioning
confidence: 99%
“…Taking the day of the hemorrhage as day 0, surgical intervals were defined either as immediate (day 0), early (days 1-3), intermediate (days [4][5][6][7][8][9][10][11][12][13][14] or late (days after 14).…”
mentioning
confidence: 99%